Continuous reinforcement operator applied to resilience in disaster rescue networks - Jassbi, Javad J. (2019)
This work was partially funded by FCT Strategic Program UID/EEA/00066/2013, project PEST of UNINOVA and also by the Fundação para a Ciência e a Tecnologia (Portuguese Foundation for Science and Technology) through theproject UID/MAT/00297/2013 (Centro de Matemática e Aplicações).